Cover Image, Volume 97, Issue 1. (January 2017) - Longo, Rocco; Blackman, John W; Torley, Peter J; Rogiers, Suzy Y; Schmidtke, Leigh M
Abstract : The cover image, by Rocco Longo et al., is based on the Review Changes in volatile composition and sensory attributes of wines during alcohol content reduction, DOI:10.1002/jsfa.7757 . Abstract : The cover image, by Rocco Longo et al., is based on the Review Changes in volatile composition and sensory attributes of wines during alcohol content reduction, DOI:10.1002/jsfa.7757 .